Broadband photodetector based on vertically stage-liked MoS2/Si heterostructure with ultra-high sensitivity and fast response speed. (February 2020) - Guo, Junxiong; Li, Shangdong; Ke, Yizhen; Lei, Zhicheng; Liu, Yu; Mao, Linna; Gong, Tianxun; Cheng, Tiedong; Huang, Wen; Zhang, Xiaosheng
Abstract: We report a broadband photodetector based on vertically stage-liked MoS2 /Si heterostructure with MoS2 sheet modified using rapid annealing technique. The fabricated photodetector features a unique structure of naturally formed band alignment in MoS2 after annealing and shows an ultra-high responsivity up to 746 mA W −1 and detectivity up to 6.03 × 10 11 Jones ranging from 405 to 980 nm, as well exhibits a fast response speed with a rise time of ∼178 µs and fall time of ∼198 µs. The demonstrated superb photodetector suggests an effective way to form vertical p-n junction for improving the performances of future optoelectronic devices. Graphical abstract: Image, graphical abstract